Marital Disputes before the Court. The Reality of Marriage 60th Years of the 19th Century in the Judicial Acts of the Prague Archbishopric (Theatrum historiae, 2016)
The study is reflecting selected matrimonial disputes of the 60s of the 19th century and is deriving from the court records of the Prague archbishopric. The introduction is briefly describing the legal framework of marriage during the 19th century. In the next part are as individual cases presented wedding disputes, another two specific cases relating to matrimonial disputes with an attempt of contemporary reflection. The study is publishing as a part of a research project “Every day life in marriage in the „long“ 19th century from Roman Catholic viewpoint“.
Keywords: marriage; court; nuptial dispute; 19th century; cultural history; gender history